Physical Activity and Its Impact on the Clinical Course and Quality of Life in Crohn’s Disease - Katarzyna Jastrowicz-Chęć; Milena Fortuna; Paulina Hetnar; Sebastian Kiper; Sławomir Toczek; Magdalena Tomala; Klaudia Koryszko; Natalia Pokrywka; Dawid Suwała; Marcelina Polak (Quality in Sport, 2025)
Introduction: Crohn’s disease is a chronic inflammatory condition belongs to the group of inflammatory bowel diseases (IBD). Due to its chronic and relapsing nature, the disease significantly impairs patients’ quality of life and negatively impacts their mental health. In recent years, there has been increasing interest in the role of physical activity as a supportive component of treatment. Aim of study: The aim of this paper is to review the current state of knowledge regarding the impact of physical activity on the clinical course and quality of life in patients with Crohn’s disease. The review focuses on the potential benefits of engaging in physical activity, as well as the possible limitations and risks associated with its implementation during different phases of the disease. The benefits of regular physical activity will be evaluated, including improvements in quality of life, reduction of disease symptoms, and support of the treatment and recovery process. The paper will discuss both the physical and psychological aspects of the impact of physical activity on patients with Crohn’s disease Material and methods: Searches were performed using the PubMed, Scopus, and Google Scholar databases. Scientific publications from the years 2005-2025 were included, focusing on the impact of physical activity on patients with Crohn’s disease and other forms of IBD. Results: Regular moderate-intensity exercise may alleviate symptoms, reduce fatigue, and improve mental health and quality of life. There is evidence suggesting that physical activity can have a beneficial effect on inflammatory processes and the risk of flare-ups. However, clear recommendations regarding the type and intensity of exercise, especially during periods of exacerbation, are still lacking. Conclusions: Physical activity is a safe and potentially effective adjunct therapy for patients with Crohn’s disease, especially during remission. However, it requires individual adjustment and further research.